Islamic Psychology-Based Educational Strategies For Student Character Development - Warsah, Idi; Morganna, Ruly; Warsah, Berliani Aslam Alkiromah; Warsah, Bizikrika Hably Hudaya (Institut Agama Islam Negeri (IAIN) Curup, 2024)
Character education is a vital component in shaping a generation with integrity and readiness to face future challenges. This study aims to identify effective models and approaches within Islamic psychology-based education strategies for student character development and to determine the success indicators of these strategies through a bibliometric review. Utilizing systematic literature reviews and bibliometric analysis, this research gathers and analyzes data from various relevant sources. The findings reveal that integrating moral and spiritual values into the curriculum significantly impacts students' development across academic, moral, spiritual, emotional, social, personal, cultural, and environmental dimensions. Effective models and approaches include fitrah-based education, tarbiyah, and akhlaq teaching, along with the involvement of parents and the community. The use of technology in character education, through Islamic psychology-based applications and platforms, also enhances student engagement and aids in the internalization of moral and spiritual values. Identified success indicators include improved academic performance, moral and ethical development, heightened spiritual awareness, engagement in social and environmental activities, and a reduction in negative behaviors. This study provides practical guidance for educators and policymakers in designing comprehensive and sustainable character education programs. Additionally, it makes a significant contribution to the academic literature by demonstrating the effectiveness of Islamic psychology-based education strategies in fostering strong and integral student character. The application of these findings is expected to assist schools and educators in cultivating a generation that is well-prepared to meet future challenges with solid character and high moral values.